Coaching advice from legendary wheelchair tennis players - Harnett, J.; Roetert, E. P. (Coaching and Sport Science Review, 2024)
This article features insights from a selected group of the most prominent and successful Wheelchair Tennis Players of all time. Therefore, this is an overview, or opinion piece, more than a traditional research article. The players that are highlighted shared their views on what it took to get to the very top of the game. All were happy to share their "secrets" in hopes of supporting tennis coaches as well as players of all levels as they strive to reach their goals. Each of these players is either a current, or future, member of the International Tennis Hall of Fame. We hope that their insights will show the individual traits of each player, but just as important their commonalities, which highlight their road to the very top of the game.